The heart of change : Real-life stories of how people change their organizations / John P. Kotter ; Dan S. Cohen - Kotter, John P.
John Kotter and co-author Dan Cohen delve deeper into the subject of change to get to the heart of how change actually happens. Through real-life stories from people in the trenches, in all kinds of organizations, the authors attack the fundamental problem that underlies every major transformation: How do you go beyond simply getting your message across to truly changing people's behavior?